The association between frequency of consumption of gluten-containing foods and caries index in children with ADHD: A cross-sectional study - Puteri, Mega Moeharyono; Tedjosasongko, Udijanto; Putri, Maudiva Tasya; Febriyanti, Iryunia; Tiongin, Arella Velika Karla; Ainistikmalia, Rania Nurin; Kumar, Krishna (Universitas Padjadjaran, 2026)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by inattention, hyperactivity, and impulsivity, which may influence dietary behaviors and oral health, particularly the risk of dental caries. Gluten-containing foods are commonly consumed by children and may contribute to cariogenic exposure, especially in children with ADHD who tend to have irregular eating habits and may have poorer oral hygiene, including less frequent toothbrushing. In addition, stimulant medications commonly prescribed for ADHD may reduce salivary flow and potentially affect salivary buffering capacity. This study aimed to assess the association between the frequency of consumption of gluten-containing foods and caries index in children with ADHD. Methods: A cross-sectional study involving 34 children aged 6–12 years diagnosed with ADHD was conducted in special needs schools in Surabaya. The frequency of consumption of gluten-containing foods was assessed using a semi-quantitative Food Frequency Questionnaire, while dental caries was assessed using the DMF-T index based on WHO criteria. Data analysis was performed using Spearman’s rank correlation test to determine the association between the frequency of consumption of gluten-containing foods and caries index. Results: The majority of children demonstrated a moderate level of consumption of gluten-containing foods and a moderate to high caries index. Statistical analysis revealed a strong and significant positive correlation between the frequency of consumption of gluten-containing foods and caries index (r = 0.989; p < 0.05), indicating that more frequent consumption of gluten-containing foods was associated with higher dental caries index in children with ADHD. Conclusion: This study showed a significant association between the frequency of consumption of gluten-containing foods and caries index in children with ADHD, suggesting that dietary habits may contribute dental caries. These findings support the importance of integrating dietary management and oral hygiene education into preventive strategies for children with ADHD.